1990
DOI: 10.1007/bf02216053
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of Org 2766, a synthetic analog of the adrenocorticotrophic hormone (4–9), in 14 outpatient autistic children

Abstract: Fourteen children (12 infantile autism full syndrome present, 2 atypical pervasive developmental disorder) between 5 and 13 years of age participated in a double-blind placebo-controlled cross-over trial. Each child received 20 mg Org 2766 (synthetic analog of ACTH 4-9)/day during 4 weeks, or placebo in a randomly assigned sequence. Drug effects were monitored by ethological playroom observation and by Aberrant Behavior Checklist ratings by parents and teachers. Data of the playroom observation pointed to an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…However, a thorough specification and detailed description of these deficits is a condition sine qua non to hypothesize and examine the psychological and neurobiological underpirmings of these deficits. Within the frame of this paper we limit ourselves to remarks on putative psychological mechanisms; discussions and speculations on relevant neurobiological issues may be found in Dawson and Lewy (1989), Van Engeland (1989), Buitelaar, Van Engeland, Van Ree & de Wied (1990), and Buitelaar et al (submitted).…”
Section: Discussionmentioning
confidence: 98%
“…However, a thorough specification and detailed description of these deficits is a condition sine qua non to hypothesize and examine the psychological and neurobiological underpirmings of these deficits. Within the frame of this paper we limit ourselves to remarks on putative psychological mechanisms; discussions and speculations on relevant neurobiological issues may be found in Dawson and Lewy (1989), Van Engeland (1989), Buitelaar, Van Engeland, Van Ree & de Wied (1990), and Buitelaar et al (submitted).…”
Section: Discussionmentioning
confidence: 98%
“…The clinical trials aimed at testing therapies that modulate the immune response in children with ASD have addressed mainly the use of steroids, intravenous immunoglobulin G, antibiotics, and vitamin D (Cannell 2008;Gupta 1999;Plioplys 1998;Pradhan et al 1999;Sandler et al 2000;Dalakas 1997;Shenoy et al 2000;Matarazzo 2002;Bradstreet et al 2007;Buitelaar et al 1990;Geier and Geier 2005). Understanding the biological effects of these treatments could probably provide a better background toward more effective conventional and alternative therapies.…”
Section: Current Directions On Immunomodulation In Asdmentioning
confidence: 98%
“…These findings supported the results of a previous double-blind, placebo-controlled crossover trial involving 14 children (aged 5-13 years) with ASD. Treatment with ACTH (20 mg/day) was noted to improve stereotypic behaviors and enhance social interaction in the subjects (Buitelaar et al 1990(Buitelaar et al , 1992b.…”
Section: Clinical Researchmentioning
confidence: 99%
“…Children with ASD have been reported to have both abnormal circulating levels and physiologic responses to ACTH (Hamza et al 2010;Marinovic-Curin et al 2008). Several controlled trials have reported ACTH to be well tolerated and result in improvement in ASD symptoms in some children (Buitelaar et al 1990(Buitelaar et al , 1992a.…”
Section: Clinical Researchmentioning
confidence: 99%